Energy-efficient strategy for work node by DRAM voltage regulation in storm - Yonglin PU; Jiong YU; Liang LU; Chen BIAN; Bin LIAO; Ziyang LI (Tongxin xuebao)
Focused on the problem that traditional energy-efficient strategies never consider about the real time of data processing and transmission,models of directed acyclic graph,parallelism of instance,resource allocation for task and critical path were set up based on the features of data stream processing and the structure of storm cluster.Meanwhile,the WNDVR-storm (energy-efficient strategy for work node by dram voltage regulation in storm) was proposed according to the analysis of critical path and system performance,which included two energy-efficient algorithms aiming at whether there were any work nodes executing on the non-critical path of a topology.Finally,the appropriate threshold values fit for the CPU utilization of work node and the volume of transmitted data were determined based on the data processing and transmission constraints to dynamically regulate the DRAM voltage of the system.The experimental result shows that the strategy can reduce energy consumption effectively.Moreover,the fewer constraints are,the higher energy efficiency is.